Le patrimoine urbain dans les vitrines des grands magasins - Nathalie Simonnot (Territoire en Mouvement)
Windows display give a lot of examples on architecture and cities showings. Used as images in windows display, recreated as models or showing buildings with the layout of the products themselves, these urban environment creations are full if imagination. The use of urban landscapes and monuments for the commercial purpose points out the importance of architecture and urban areas in a popular heritage composition that could be considered as an architectural museum.